A objetivação do sujeito “homem do campo” no especial publicitário “Chevrolet – Na estrada com quem faz” - Santos, Tatiana Batista dos (2024)
The present research aimed to analyze how the objectification of the “rural man” subject occurs through media discourse, especially in automotive advertisements pieces whose target audience is rural entrepreneurs. The corpus of this research consists of 12 extended episodes of the advertising special “Chevrolet - On the road with those who make it happen”, published on the G1 news portal page dedicated to the campaign, from January to December 2020. Then, this research is is based on Foucauldian Discourse Studies as a theory and method of analysis, in order to identify discursive sequences in which the “rural man” subject is objectivized, which subjects are called to occupy this place and which ones are silenced in this discourse. Thus, the aim was to observe the power and knowledge relations that permeate and constitute media statements about brazilian agribusiness in favor of inscribing a discursivity aimed at/about the “rural man”. Given the role and importance of agriculture in Brazil and the historical conditions of possibility at the time of the campaign’s exhibition, it was important to reflect on how media discourse affects the production of truth effects about and for the rural man subject. As an analytical approach, we chose collating the statements through topical paths. After carefully listening to the episodes in question, the analysis was divided into five paths, namely: i) from a difficult childhood to entrepreneurship: stories of overcoming; ii) sustainability: productivity at the expense of environmental responsibility; iii) the importance of family and succession: continuing a legacy; iv) educational: the importance of being prepared and v) technology: “agriculture is tech” just like the new S10. The reduction of the rural man to a single representative simplifies the diversity of the rural environment, contributing to the standardization and limitation of the view of this subject, erasing other realities such as those of family farmers, small producers, and less privileged groups. The analysis reflects that these subjects are objectivized, therefore, discursively constituted, through the intersection of discourses sustained by a neoliberal rationality that is prevalent in contemporary society. This rationality manifests in the emphasis on efficiency and the pursuit of individual success, shaping the image of the rural man as an agile and competitive entrepreneur. Additionally, patriarchal discourses and their relations with the logic of meritocracy reinforce the idea that the rural man’s success is the result of individual effort and merit, disregarding structural inequalities and the power relations that permeate the field. The sustainability discourses, which align with a capitalist discourses, promote a vision of the rural man as a conscientious and responsible agent who adopts environmentally friendly agricultural practices. However, this often serves to mask the negative environmental impacts of agribusiness. Lastly, the emphasis on technology and the modernization of the countryside reinforces the image of the rural man as an innovative subject who adapts to the demands of the global market, without considering the social and cultural implications of this accelerated modernization.